Gambaran Perencanaan dan Pengadaan Obat di Puskesmas Rawat Jalan Kabupaten Rokan Hulu Tahun 2018 - septia roza; erniza pratiwi (Jurnal Penelitian Farmasi Indonesia, 2019)
A study was conducted on the description of drug planning and procurement at outpatient health centers in Rokan Hulu Regency in 2018. The purpose of this study was to look at the description of drug planning and procurement at outpatient health centers in Rokan Hulu Regency in 2018 referring to Permenkes number 74 years 2016 and see the suitability of the implementation of planning and procurement in outpatient health centers in Rokan Hulu Regency. This type of research is quantitative descriptive observational with a retrospective data collection from January to December 2018. The sample used was 13 outpatient health centers and 80 drug samples in the LPLPO. The results of his research are based on the Permenkes assessment element number 74 of 2016, the overall outpatient puskesmas drug planning system meets the requirements with a percentage of 97.43% with a very good category and the drug procurement system has reached 100%. Based on the results of conformity assessment, the suitability of drug planning reaches a percentage of 90.3% and suitability of drug procurement reaches a percentage of 79.90%.